ANALISIS RANTAI PASOK BIJI KOPI ROBUSTA DI KECAMATAN TAMBORA KABUPATEN BIMA - Yusuf, Muhammad; Septiadi, Dudi (Fakultas Pertanian Universitas Mataram, 2023)
The aims of this research are to: (1) Analyze the robusta coffee bean supply chain network in Tambora District, Bima Regency; (2) Analyze the performance of the robusta coffee bean supply chain in Tambora District, Bima Regency. The research uses descriptive methods, while data collection is carried out using survey techniques. Data is analyzed descriptively using Food Supply Chain Network (FSCN) and Supply Chain OperatingReference (SCOR) framework analysis. The results of the research show that: (1) The robusta coffee bean supply chain network in Tambora District, Bima Regency is: (a) The final target of the robusta coffee bean supply chain is within and outside the island (Lombok and Java) while the development targets are paying attention to grade levels, cut one of the supply chain actors and equalize prices; (b) Supply chain management consists of selecting partners based on location proximity, size of purchasing scale and ease of marketing robusta coffee beans. Agreements that occur between links in the chain are carried out informally (orally) with cash transactions. Lack of assistance from the government for robusta coffee bean supply chain actors; (c) The supply chain structure includes 2 channels, namely channel I (farmers - village collectors - village collectors - sub-district collectors - wholesalers - inter-island traders) and channel II (farmers - village collectors - large traders - off-island traders (Lombok and Java) where each supply chain has a different role. The supply of robusta coffee beans from the Tambora District, Bima Regency has not been able to meet the demand of the processing industry; (d) Supply chain resources consist of physical resources that are different for each member of the chain according to the activities carried out, technological resources still use simple equipment, human resources use labor within and outside the family and capital resources are still limited using own capital and loans; (e) The supply chain business process consists of 3 streams, namely product flow, fund flow and information flow which are distributed evenly and smoothly. The risks faced by each link in the chain are related to fluctuating prices, damage to production results and market congestion and the way to build trust is to communicate smoothly and sell to the same actors. (2) Robusta coffee bean supply chain performance which is in a superior position that must be maintained, namely perfect order fulfillment, delivery performance and asset management (channels I & II), order fulfillment cycle and flexibility. The performance that must be further improved to a superior position is the order fulfillment cycle (parity) and flexibility (advantage) in channel II with the costs incurred by channel I being greater than those of channel II.